Corporate Social Responsibility (CSR) practices of financial institution in Bangladesh: the case of United Commercial Bank - Afrin, Sumaiya; Sehreen, Farhana; Polas, Mohammad Rashed Hasan; Sharin, Rubyat (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: The main purpose of the research is to understand the CSR practices of financial institutions in Bangladesh better. Research methodology: Corporate Social Responsibility (CSR) is concerned with businesses’ interactions with society as a whole. Such CSR operations cover an organisation’s fiscal, legal, ethical, and philanthropic obligations. United Commercial Bank Limited (UCB) has been chosen as the study’s subject. This study is a qualitative research project that used an exploratory research design. For data collection, both main and secondary data sources were used. The in-depth interview approach with an open-ended questionnaire was used to gather primary data on CSR practices from 70 UCB employees. Results: According to the findings of the study, UCB is deeply performing its fiscal, legal, ethical, and philanthropic responsibilities, but it has not expanded its philanthropic activities on a voluntary basis. Furthermore, the representation of UCB employees in CSR management is inadequate, with the exception of top-level executives. Limitations: Any methodological issues were addressed, such as sampling challenges because financial institutions do not encourage third parties to obtain their secrets because competition occurs everywhere. Contribution: This study makes several suggestions, such as improved and more systematic communication of CSR strategies to employees, increased investments in CSR programs, and specially targeted CSR preparation, which could assist UCB in encouraging a more successful application of its CSR strategies.